Nascimento de parto cesáreo, depressão e transtorno bipolar em adolescentes de uma coorte de nascimento, São Luís –MA. - COELHO, Sâmia Jamile Damous Duailibe de Aguiar Carneiro (2019)
INTRODUCTION: Birth by cesarean section has been investigated as risk for development of mood disorders in the offspring. OBJECTIVE: The present research aimed to investigate if there is a causal association between birth by cesarean section and development of depression and bipolar disorder in teenagers. METHOD: It was a cohort study that evaluated 1.603 teenagers, in the year of 2016, that participated of the third phase of the cohort RPS study in São Luís –MA. At birth, were investigated type of birth, birth weight, prematurity, maternal age, maternal educational level, parity, conjugal status and smoking during pregnancy. In the teenagers, were investigated gender, skin color, study at present, religion, separated parents, family’s income, smoking and alcohol use. The outcome variables were depression and bipolar disorders and the construct mood disorder. A Directed Acyclic Graph (DAG) was constructed to select the variables for minimum adjustment for confounding. In the analysis, was used estimationthrough weighting by propensity score. RESULTS: There was no statistical difference regarding type of birth and depression (CI 95% -0,035;0,019/p=0,55), bipolar disorder (CI 95% -0,022; 0,042/p=0,53)and mood disorder (CI 95% -0,034; 0,039/p=0,89) in teenagers, in both sexes. CONCLUSION:In the present study, no associationwas observed between cesarean section and development of depression and bipolar disorder in teenagers.